Comparative Study of the teaching styles of Social Sciences University professors from Spain and Brazil - Carbonero, Miguel Angel; Martín-Antón, Luis Jorge; Flores, Valle; Freitas Resende, Alvaci (Revista Complutense de Educación, 2016)
Knowledge about the psychoinstructional characteristics of university professors’ teaching styles is essential to improve the training quality received by their students. Given the current level of globalization and student exchange among countries, this analysis requires a global vision that provides lines of research on which to base programs to improve teaching efficacy in higher education. In order to determine possible differences in the variables that define teaching styles and their impact on instructional models, we selected a sample of Spanish (n = 102) and Brazilian (n = 103) university professors from the knowledge areas of social sciences, also taking gender into account. For this purpose, we applied the "Cuestionario de Evaluación de las Variables de los Estilos de Enseñanza en la Educación Superior" (CEVES [Assessment Questionnaire of Teaching Style Variables in Higher Education]), which measures: organization, communication, social skills, conflict resolution, and management of the teaching processes; and the "Cuestionario de Evaluación de la Metodología Docente y Evaluativa de los Profesores Universitarios (CEMEDEPU [Questionnaire to assess University Teachers’ Teaching and Evaluative Methods]), which analyzes instructional models focused on teaching, learning, and teacher skills. The results of a multivariate analysis of variance, considering country and gender as independent variables, showed that the Brazilian professors obtained higher scores in social skills, conflict resolution, and management of the teaching processes. In both groups, we found positive correlations between the instructional variables and a model focused on learning but in the Spanish professors, we observed negative correlations between the instructional variables and a model focused on teaching. There were no differences as a function of gender. Consequently, it is necessary to implement instructional programs to improve Spanish teachers’ socioemotional variables, while underlining the importance of teaching, to guarantee the unification of the teaching competences of university professors.